Pancasila as the foundation of Science Policy in Indonesia - Sumarwoto Sumarwoto (Universitas Muhammadiyah Gresik, 2022)
Pancasila as the basic value of Science Development explains that every science and technology (iptek) developed in Indonesia must not conflict with the values contained in Pancasila. science and technology itself develops autonomously, then in the course of adaptation to the values of Pancasila. Every science and technology developed in Indonesia must include the values of Pancasila as an internal factor in the development of Science and technology itself. The method used in this study is empirical juridical the results of this study explain that a clear orientation is needed to filter and counteract the influence of global values that are not in accordance with the values of the personality of the Indonesian nation. Some of the reasons Pancasila is needed as the basic value of the development of Science and technology in the life of the Indonesian nation include environmental damage caused by science and technology, a means to control and control the progress of Science and technology, the values of local wisdom that became a symbol of life in various regions. Lmu development policy in Indonesia can be seen from historical sources, sociological sources and political sources.